Natural Disaster Mapping on Java Island Using Biplot Analysis - Widyangga, Pressylia Aluisina Putri; Mardianto, M. Fariz Fadillah; Pratiwi, Firda Aulia; Putrie, Andi Vania Ghalliyah; Andriani, Putu Eka; Amelia, Dita; Dewi, Deshinta Arrova (Universitas Bumigora, 2024)
Indonesia is located in the ring of fire region. This condition causes Indonesia to have the potential to experience various disasters, such as volcano eruptions. In addition, rapid population growth has led to rampant land conversions that cause floods, landslides, tornadoes, droughts, and forest fires. The research aims to map natural disasters in Indonesia, especially Java Island to find out the provinces and their natural disasters tendency using Biplot analysis. Based on the results, Central Java, East Java, and West Java have a tendency to have floods and landslides. East Java tends to undergo earthquakes and Central Java has the potential to experience volcano eruptions. Through the natural disasters mapping, the government, especially the BMKG, will be able to find various solutions to overcome the natural disasters that have great potential to occur in provinces in Indonesia, especially Java Island as the manifestation toward SDGs Target 2030.